Cloning and Expression of Fimbrial Subunit Gene Of Pasteurella Multocida Type 6: B, Isolated From Cattle With Haemorrhagic Septicaemia - Ali, Ernie Zuraida (2005)
Haemorrhagic septicaemia (HS) is a common disease of cattle and buffaloes, particularly in Asia. In Malaysia, PasteureIIa muItocida 6:B is most commonly isolated from outbreaks of haemorrhagic septicaemia. Thus, many antigenic components of P. multocida have been studied such as the lipopolysaccharides (LPS), outer membrane proteins (OW) and the capsule. However, the fimbriae, which is involved in the attachment to the cell surface of the host and usually correlated with virulence of the organism has not been studied. Thus, studies on fimbrial gene and protein may be essential in the production of vaccine against haemorrhagic septicaemia. In this study, fimbriae gene of P. muItocida type 6:B was amplified, cloned and subjected for sequencing and expression in Pseudomonus ueruginosa and Eshericheriu coli. All isolates produced a single product approximately at 450 bp. Analysis of the fimbrial subunit gene sequence of type 6:B strain was compared with those of type A:l and A:3 strains of P. rnultocida. The sequence of strains A:3 and 6:B showed complete homology while the sequence of strains A:l and 6:B showed 81.8% amino acid similarity. Although the P. multocida and other species shared that mean showed the conserved same mature fimbriae, both showed different signal peptides, even though they were within the same groupltype. Pasteurella multocida fimbrial subunit gene was cloned in the expression vectors, pUCpKS/SK and pCRT7-TOP0 in order to construct a recombinant plasmid. In SDS-PAGE gel, it was seen that the recombinant P. aeruginosa cells failed to produce fimbriae using a specific surface fimbriae method. On Western blot analysis using anti-P. aeruginosa fimbrial antiserum, reaction was observed in both the wild type P. aeruginosa and the whole cells of recombinant P. aeruginosa cells. However, only the wild type P. aeruginosa showed cross-reaction when probed with anti-P. multocida fimbrial antiserum. This indicated that the wild type P. aeruginosa shared the same epitope with P. multicoda and that the fimbriae proteins of P. multocida was not expressed in P. aeruginosa. In E. coli cells, the recombinant protein was expressed as a soluble protein but at a relatively low level despite optimization. In the Western blot analysis using anti-P. multocida fimbrial polyclonal antibody, the recombinant protein was identified as the protein band that have a molecular weight of approximately 18 kDa. However, it was uncertain whether the endogeneous fimbriae was not expressed or the protein was expressed but was not exported out of the cell. Thus, hrther analysis to identify the other candidate genes and to try with other suitable hosts are required